Weed control assessed visually and by aerial images (Revista Brasileira Multidisciplinar, 2021)
The employment of remotely piloted aircraft (RPA) for obtaining images in the field has grown and can assist the of management of weeds, however, the software for analysis and processing of images need to be tested under different conditions for the development of routines and validation of results. Therefore, the objective of this work was to correlate the results of the methodology of visual assessment (using scale of notes) with the results of the processing of aerial images with the software SisCob® and ImageJ® for the analysis of the occurrence and effectiveness of weed control. The comparisons were made in ten areas with different levels of weed infestation. A fallow area with four months has been submitted to the different treatments of chemical control with glyphosate herbicide, including a control without application, varying application rate (50, 90 and 150 L ha-1), the addition of adjuvant and presence of electrostatic spray. After 35 days of herbicide application, each area was assessed visually, and, in parallel, the area was overflied done the overflying the area with a RPA for image collection and subsequent digital processing, using both softwares for quantification in percentage of the control with the herbicide. All tested correlations (Pearson, Spearman and Kendall) were significant and positive, indicating that the use of RPA for image collection and their processing by means of the software demonstrated potential as an alternative for the evaluation of weed control, which may replace the visual assessment with operator in the field, avoiding the subjectivity and slowness in the evaluations.
Keywords: Precision Agriculture; Agricultural Monitoring; Weeds; Image Processing